Micro-fractionation shows microbial community changes in soil particles below 20 μm - Keuschnig, Christoph; Martins, Jean M. F.; Navel, Aline; Simonet, Pascal; Larose, Catherine (Frontiers in Ecology and Evolution, 2022)
Micro-scale analysis of microbes in soil is essential to the overall understanding of microbial organization, interactions and ecosystem functioning. Soil fractionation according to its aggregated structure has been used to access microbial habitats. While bacterial communities have been extensively described, little is known about the fungal communities at scales relevant to microbial interactions. Here we studied fungal and bacterial communities as well as nitrogen cycling potentials in the pristine Rothamsted Park Grass soil (bulk soil) as well as in its particle size fractions (PSFs; > 250 µm, 250-63 µm, 63-20 µm, 20-2 µm, < 2 µm and supernatant). Microbial communities changed in PSFs below 20 µm at the scale where microbes operate and interact, highlighting the potential to focus on little researched sub-fractions of micro-aggregates. The relative abundance of Basidiomycota decreased with decreasing particle size, while Ascomycota showed an increase and Mucoromycota became more prominent in particles below 20 µm. Bacterial diversity was found highest in the < 2 µm fraction, but only a few taxa were washed-off during the procedure and found in supernatant samples. These taxa have been associated with exopolysaccharide production and biofilm formation (e.g., Pseudomonas, Massilia, Mucilaginibacter, Edaphobaculum, Duganella, Janthinobacterium and Variovorax). The potential for nitrogen reduction was found elevated in bigger aggregates. The applied method shows potential for use in studies focusing on the role of microbial biofilms in soil and might also be adapted to research various other soil microbial functions. Technical advances in combination with micro-sampling methods promise valuable output in soil studies when particles below 20 µm are included.